2011
DOI: 10.1542/peds.2010-3007
|View full text |Cite
|
Sign up to set email alerts
|

Decision-Making Around Gastrostomy-Feeding in Children With Neurologic Disabilities

Abstract: Values associated with gastrostomy-feeding and feeding by mouth, the context of child and family, and the process of decision-making facilitated by the health care system shape parental experiences and decisional conflict. This framework will help guide interventions, such as patient decision aids, that are aimed at improving parental decision-making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
75
1
16

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(92 citation statements)
references
References 31 publications
0
75
1
16
Order By: Relevance
“…1 G-tubes allow nutrition to be provided directly into the stomach and are typically placed to mitigate nutritional or respiratory complications of swallowing dysfunction. [2][3][4] Given the symbolic significance of feeding as a parental duty 5 and the impact of this intervention on the child's daily life, 6 decisions regarding the placement of a G-tube are often complex. Many clinical practice guidelines recommend G-tube feeding largely based on evidence demonstrating its effectiveness on nutritional outcomes 2,3,7 without a comprehensive understanding of the patient-centered outcomes that are critical for family decisionmaking.…”
Section: What's Known On This Subjectmentioning
confidence: 99%
See 1 more Smart Citation
“…1 G-tubes allow nutrition to be provided directly into the stomach and are typically placed to mitigate nutritional or respiratory complications of swallowing dysfunction. [2][3][4] Given the symbolic significance of feeding as a parental duty 5 and the impact of this intervention on the child's daily life, 6 decisions regarding the placement of a G-tube are often complex. Many clinical practice guidelines recommend G-tube feeding largely based on evidence demonstrating its effectiveness on nutritional outcomes 2,3,7 without a comprehensive understanding of the patient-centered outcomes that are critical for family decisionmaking.…”
Section: What's Known On This Subjectmentioning
confidence: 99%
“…5 Research about shared decision-making has found that adequacy of information is a potentially modifiable component that can decrease decisional conflict among patients and families. 8 Furthermore, the same themes can be revisited after the procedure to enhance family support.…”
Section: What's Known On This Subjectmentioning
confidence: 99%
“…21 The decision to commence tube feeding is complex for families and carers of children with CP and may be filled with decisional conflict. 22,23 The values and meanings of feeding and eating are much more complex than simply providing adequate nutrition and maintaining weight gain. 23 A balanced and sensitive approach to informing parents and carers regarding the risks and benefits of enteral tube feeding and exploration into how tube feeding will fit into the context of everyday life is essential to assist in the decision-making process.…”
Section: Nutrition Supportmentioning
confidence: 99%
“…22,23 The values and meanings of feeding and eating are much more complex than simply providing adequate nutrition and maintaining weight gain. 23 A balanced and sensitive approach to informing parents and carers regarding the risks and benefits of enteral tube feeding and exploration into how tube feeding will fit into the context of everyday life is essential to assist in the decision-making process. 22 The choice of access for enteral tube feeding will depend upon the anticipated duration of feeding and the clinical status of the child.…”
Section: Nutrition Supportmentioning
confidence: 99%
“…This research emphasizes the importance of understanding the symbolic meanings of GFTs in relation to maternal identity, the maternal role, food, feeding, eating and child development. [17][18][19][20][21][22] FEEDING AND THE MOTHERING ROLE The suggestion of a GFT may challenge the 'good mother narrative' and signify maternal failure. Mothers may blame themselves for the child's inability to feed and poor growth or feel blamed by members of the extended family.…”
Section: Introductionmentioning
confidence: 99%